Impact of I(SK) Voltage and Ca(2+)/Mg(2+)-Dependent Rectification on Cardiac Repolarization - Bronk, Peter (Biophys J, 2020)
Cardiac small conductance Ca(2+)-activated K(+) (SK) channels are activated solely by Ca(2+), but the SK current (I(SK)) is inwardly rectified. However, the impact of inward rectification in shaping action potentials (APs) in ventricular cardiomyocytes under β-adrenergic stimulation or in disease states remains undefined. Two processes underlie this inward rectification: an intrinsic rectification caused by an electrostatic energy barrier from positively charged amino acids at the inner pore and a voltage-dependent Ca(2+)/Mg(2+) block. Thus, Ca(2+) has a biphasic effect on I(SK), activating at low [Ca(2+)] yet inhibiting I(SK) at high [Ca(2+)]. We examined the effect of I(SK) rectification on APs in rat cardiomyocytes by simultaneously recording whole-cell apamin-sensitive currents and Ca(2+) transients during an AP waveform and developed a computer model of SK channels with rectification features. The typical profile of I(SK) during AP clamp included an initial peak (mean 1.6 pA/pF) followed by decay to the point that submembrane [Ca(2+)] reached ∼10 μM. During the rest of the AP stimulus, I(SK) either plateaued or gradually increased as the cell repolarized and submembrane [Ca(2+)] decreased further. We used a six-state gating model combined with intrinsic and Ca(2+)/Mg(2+)-dependent rectification to simulate I(SK) and investigated the relative contributions of each type of rectification to AP shape. This SK channel model replicates key features of I(SK) recording during AP clamp showing that intrinsic rectification limits I(SK) at high V(m) during the early and plateau phase of APs. Furthermore, the initial rise of Ca(2+) transients activates, but higher [Ca(2+)] blocks SK channels, yielding a transient outward-like I(SK) trajectory. During the decay phase of Ca(2+), the Ca(2+)-dependent block is released, causing I(SK) to rise again and contribute to repolarization. Therefore, I(SK) is an important repolarizing current, and the rectification characteristics of an SK channel determine its impact on early, plateau, and repolarization phases of APs.